Stomatopods (Crustacea: Hoplocarida) from the Gulf of Tehuantepec, Mexico - Barbosa-Ledesrna, I F; Gamboa-Contreras, J A; Aké-Castillo, J A (Revista de Biología Tropical, 2000)
A total of 1 173 specimens of Stomatopoda were captured in 27 localities at different depths (20 to 73 m) during three oceanographic cruises in the Mexican Pacific along the continental shelf of lhe states of Oaxaca and Chiapas. Seven species were identified of the familíes EurysquiHidae, Lysiosquillidae and Squillidae. Squil/a hancocki and Squilla parva were the most abundant species and the most frequently found together. The relationships between total lenglh and carapace length were obtaíned for these specíes, which show that males of S. hancocki have a longer carapaee length than females having the sarne total length, whereas for S. parva the opposite oecurs. Larger sizes than previously reported were obtained for Lysiosquilla panamica and Squilla malltoidea. Squilla bigelowi was recorded for the first time in the Gulf of Tehuantepec. AH the speeies were found in the intermediate platform (25-60 m); E. veleronis, S. hancocki and S. parva extended their distributions to the extemal platform (60-120 m), and S. hancocki and S. parva reached the circalittoral zone (10-25 m).